Republic of Poland : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper and Statistical Appendix analyzes fiscal costs associated with Poland's accession to the North Atlantic Treaty Organization and European Union (EU). The paper highlights that Poland's accession to the EU could result in fiscal costs in certain areas, especially in upgrading the infrastructure in transportation and utilities, and improving the environment. The legislative reforms and the establishment of the regulatory and administrative structures are also likely to entail costs, though these costs are more difficult to quantify. This paper also discusses fiscal management and restructuring in Poland.